2021
DOI: 10.1111/jan.14994
|View full text |Cite
|
Sign up to set email alerts
|

Nursing practice environment and employee silence about patient safety: The mediating role of professional discrimination experienced by nurses

Abstract: Aims: To examine the associations between nurse work environment with nurses' silence about patient safety and the mediating effects of professional discrimination experienced by nurses. Design: Multicentre cross-sectional study. Methods: Between January and April 2019, 607 nurses and nursing assistants from seven hospitals in Greece assessed their clinical environment using the 'Practice Environment Scale of the Nursing Work Index Revised-PES-NWIR', and the silence about patient safety. The 'Experiences of Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 81 publications
0
14
1
Order By: Relevance
“…In this study, the amount of silence regarding patient safety was 2.62 ± 0.98, which was higher than the study by Kritostakis et al (5) and Lee et al (18).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In this study, the amount of silence regarding patient safety was 2.62 ± 0.98, which was higher than the study by Kritostakis et al (5) and Lee et al (18).…”
Section: Discussioncontrasting
confidence: 74%
“…The professional discrimination experienced by nurses was measured with a question from the professional discrimination self-report instrument of Krieger et al This tool has already been used in the study of Kritostakis (5) to measure the professional discrimination experienced by nurses. This question can be answered using a 5-point Likert (never: 1 to most of the time: 5 points).…”
Section: Professional Discrimination Experienced By Nursesmentioning
confidence: 99%
“…In addition, our study did not evaluate qualitatively the CM platform to identify barriers to safe communication between the teams and ensure effective communication between all portions of the team. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the incidence of depression among nurses ranged from 27.7% to 52.5% which was as high as the prevalence of hypertension and hyperlipidemia (Alkebsi et al, 2018;Chang et al, 2011;Hemmati et al, 2021;Kim et al, 2017;Zheng et al, 2021). All of these health issues among nurses are associated with the deterioration of quality of care and poor patient outcomes (Brešan et al, 2021;Kritsotakis et al, 2022). In addition, some health problems are cumulative, and the impact on the health will last until retirement, and even affect the next generation due to the damage to the reproductive system (Dumas et al, 2021;Rada et al, 2020;Zhang et al, 2020).…”
Section: Backg Rou N Dmentioning
confidence: 99%